A systematic review with evidence mapping of supportive care interventions for melanoma patients and caregivers - Jake R. Thompson; Rehana A. Salam; Sarah Hanna; Mbathio Dieng; Robyn P. M. Saw; Iris Bartula (Cancer Medicine, 2023)
Abstract Aim We conducted a systematic review and evidence gap mapping to explore the existing supportive care interventions and their impact on well‐being outcomes for melanoma patients and caregivers. Methods We searched MEDLINE, Embase, Web of Science Index Medicus, CINAHL, Lilacs, CENTRAL (Cochrane Library) and PsycINFO in December 2022, including interventional studies assessing the effectiveness of any supportive care intervention among melanoma patients and/or their caregivers. Findings Twenty studies were included in this review. These studies consisted of randomised controlled trials (n = 11, 55%), pre‐post studies (n = 7, 35%) and quasi‐experimental trials (n = 2, 10%). All studies originated from high‐income countries and focused primarily on melanoma patients, with no studies identified that focused solely on caregivers. Educational interventions were the most common (n = 7, 35%), followed by psychoeducational interventions (n = 6, 30%) and psychotherapeutic interventions (n = 4, 20%). Nearly all included studies (n = 18, 90%) reported a positive effect of the intervention on the primary outcome of interest; however, most studies (n = 17, 85%) were judged to be at moderate or high risk of bias. Due to heterogeneity of study designs, intervention characteristics and outcome measures, meta‐analysis was not conducted. Implications Supportive care interventions have positive impacts on melanoma patient well‐being outcomes, while being acceptable and feasible to conduct. More research is needed regarding supportive care interventions for melanoma caregivers. Future research should focus on eliminating sources of bias through rigorous methodology, with the development of standardised outcome measures for psychosocial outcomes to facilitate future meta‐analyses.